Clinical outcome of CAD/CAM overlays of MIH affected young permanent molars - Alaa M. Eldehna; Ayat G. Montaser; Shaimaa A. ALrafee; Asmaa Abdelgawad (Elsevier, 2023)
Background: Restoration of first permanent molars with MIH is considered a challenge for dentists because the enamel has less flexibility and hardness with increased porosity and organic content. Materials and methods: The current study was a randomized control trial in which fifty-two first permanent molars were distributed equally into two groups (Z) teeth that received zirconia overlays and (EC) teeth that received IPS e.max CAD overlays. Clinical assessments were carried out at baseline, 6, and 12 months using modified FDI World Dental Federation criteria. Results: After the observational period of one year, all restorations were still in function with no significant differences in the esthetic, functional, and biological performance of overlays fabricated with zirconia and IPS e.max CAD except one case have been fractured in the group (EC) and three cases have been de-bonding in the group (Z). Conclusions: Using monolithic zirconia and IPS e.max CAD overlays could be a viable selection for restoring MIH-affected posterior teeth. In further studies, it is advisable to assess the restoration that combines strength with adhesive properties like zirconia-reinforced lithium silicate glass ceramic restoration.